EFEK SUPLEMENTASI AKSELERATOR PADA SILASE LIMBAH TANAMAN SINGKONG TERHADAP NILAI FLEIGH KADAR ASAM SIANIDA DAN KUALITAS FISIK - Komalasari; Liman; Syahrio Tantalo YS (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
This research aims to determined: 1) the effect of suplementation lactic acid bacterial inoculant, cassava flour, as well as a combination of lactic acid bacterial inoculant and cassava flour to the fleigh value, level of cyanide, and physical qualities in crop waste cassava silage; 2) the best suplementation to the fleigh value, level of cyanide, and physical qualities in crop waste cassava silage.  The research was conducted in August-September 2014 in the Laboratory of Nutrition and Feed Livestock, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a Completely Randomized Design (CRD). Data were analyzed by Analysis of Varians and continued with Least Significant Difference Test (LSD) 0.01.  The results showed that the best value fleigh silage was on combination treatment of lactic acid bacteria inoculants and cassava flour (p <0.01). The lowest level of cyanide silage was on cassava flour treatment (p <0.01). Treatments did not have a different effect on the physical qualities of the silage. The whole silage had a distinctive sour scent, textured crumb, not clot, green-brown, and not moldy. Based on these results it could be seen that the addition of various accelerators produced very good qualities silage so that the application could be given one of these accelerators.